Seasonal Assessment of Chemical and Physical Characterization of Khabur River, Zakho District, Kurdistan Region/Iraq -A Case Study - Al- Barwary, Musher R. A. (Science Journal of University of Zakho, 2021)
The river Khabur, the life line of more than 500 thousand of people, supplies water for the important requirements of life. In this work, a total of 192 samples of water were collected at Khabur River, Zakho District. The samples were collected monthly at four different seasons like spring, summer, autumn and winter from March, 2019 to February 2020. The samples of water were examined for total hardness (TH) , total alkalinity (TA),  pH, Calcium( Ca2+) , Electrical conductivity (EC), Nitrate (NO3-), total dissolved solids (TDS), Sulfate (SO4 2−) , phosphate, magnesium (Mg2+) BOD, and DO according to the standard methods . The results of the chemical and physical characteristics indicate the water river samples with the following parameters. The total mean values of temperature ranged from (14.461± 14.1469) oC , pH varied from (7.831 ± 0.2842). Conductivity ranged from (560. 25 ±110. 805) µS/cm).Total alkalinity varied from (194.19 ± 69.591) mg/L. Total dissolved solids varied from (355.99 ±71.581) mg/L. Dissolved oxygen varied from (8.219 ± 0.7989) mg/L. Biochemical oxygen Demand (BOD) ranged from (9.857± 6.0760) mg/L. Total hardness varied from ( 535.02 ±78.014) mg/l. Calcium (Ca2+)  varied from (409.19 ± 46.875) mg/l. Magnesium (Mg2+) ranged from ( 127.58 ± 46.875) mg/L. Chloride (CL-) varied from ( 26.938 ± 21.2133) mg/L. Nitrate (NO3-) ranged from ( 4.449 ± 2.0327) mg/L. Sulfate (SO4 2−) varied from( 43.24 ±22.479) mg/l. And phosphate ranged from (4.839 ± 1.9139) µg/L. Gradual increase in total alkalinity and hardness towards the downstream is, due to effluents in the Khabur River. Untreated from sewage discharge on river water it causes of high organic matter, phosphate and Nitrate, at high contents in Khabur River .TDS and EC were found moderate in all locations at Khabur River. The total hardness exceeded the permissible limit in all sites. The (Ca2+) and (Mg2+) were exceeded the permissible limit in all sites. In the present study an attempt had been made to determine the levels of wastewater that ultimately discharged into Khabor River without proper treatment.
Keywords: Waste water; Khabur River; Physical and chemical parameters; Zakho city